2018
DOI: 10.1007/s12015-018-9850-9
|View full text |Cite
|
Sign up to set email alerts
|

Kinin-B2 Receptor Activity in Skeletal Muscle Regeneration and Myoblast Differentiation

Abstract: The bioactive peptide bradykinin obtained from cleavage of precursor kininogens activates the kinin-B2 receptor functioning in induction of inflammation and vasodilatation. In addition, bradykinin participates in kidney and cardiovascular development and neuronal and muscle differentiation. Here we show that kinin-B2 receptors are expressed throughout differentiation of murine C2C12 myoblasts into myotubes. An autocrine loop between receptor activation and bradykinin secretion is suggested, since bradykinin se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…The B2 receptor is activated by BK and kallidin. Kinin receptors are expressed in a wide variety of cells and tissues [92–96]. The B1 receptor is not highly expressed under normal conditions, but its expression increases in the context of oxidative stress and the presence of pro‐inflammatory factors.…”
Section: Kallikrein‐kinin System In Glioblastoma‐msc Interactionsmentioning
confidence: 99%
“…The B2 receptor is activated by BK and kallidin. Kinin receptors are expressed in a wide variety of cells and tissues [92–96]. The B1 receptor is not highly expressed under normal conditions, but its expression increases in the context of oxidative stress and the presence of pro‐inflammatory factors.…”
Section: Kallikrein‐kinin System In Glioblastoma‐msc Interactionsmentioning
confidence: 99%
“…Studies have found that myogenic lineage progression is controlled by some myogenic regulatory factors (MRFs), mainly containing myogenic factor 5, myogenic differentiation (MyoD), and myogenin (MyoG) . Many other factors influence these MRFs, such as microRNAs (miRNAs), circular RNAs, and receptor proteins …”
Section: Introductionmentioning
confidence: 99%
“…9,10 Many other factors influence these MRFs, such as microRNAs (miRNAs), circular RNAs, and receptor proteins. [11][12][13][14][15][16] MiRNAs, a class of 21-nucleotide noncoding RNAs, regulate multiple biological processes. 17 MiRNAs regulate target genes by binding to the 3 ′ -untranslated region (3′-UTR) of messenger RNAs (mRNAs) to inhibit translation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from members of our group shows that BK and B2R possibly play a role in the in vitro differentiation of myoblasts towards skeletal muscle (80). In this work, Alves and collaborators report impaired skeletal muscle regeneration of B2R knockout mice that underwent induced lesion.…”
Section: Figure 3 Schematic Representation Of Signalling Cascade Trimentioning
confidence: 62%
“…Our group has studied, over the years, the mechanisms through which KKS (kininkallikrein system and its receptors) modulates key cellular processes in neurons, such as cell proliferation (83) and differentiation (74,76,77,79,135). Moreover, additional unpublished data from our group (80) and by others (102) suggests that BK aids skeletal muscle regeneration and differentiation. Considering these data and the preponderant effects that BK has on cardiovascular homeostasis, this study has sought understanding a possible impact of BK over the maturation of cardiomyocytes differentiated from hiPSC sources.…”
Section: Effect Of Modulation Of B2r On the Molecular Maturation Of Hmentioning
confidence: 95%